Variation Works Under UAE Law and FIDIC Contracts - Mardini, Sara (2025)
This study addresses a crucial issue of the variation works in construction projects, and its objective is to have insight into how the variation is controlled under and by the UAE law and FIDIC contracts. It focuses on the major distinctions between the two legal systems and stresses the need for well-defined difference clauses in contracts to avoid disputes in the course of the implementation of projects. Changes are a fact of life, and sometimes they are uncontrollable, as in the case of large projects where the changes in scope, time, or cost are constantly changing. Investigating the reasons for such variation, this paper aims to explain the effects of variation on all parties concerned, the owner, the contractor, and the consultant, especially when there is a conflict. An understanding of variations and how variations are to be put into play can go a long way in minimising disputes and will undoubtedly ensure more streamlined project delivery for all stakeholders. Keywords: variation works, construction projects, UAE law, FIDIC contracts, contractual disputes, scope changes